Law-abiding state and the legal system: correlation and interrelation (Journal of actual problems of jurisprudence, 2021)
The legal system of the Republic of Kazakhstan is in dynamic development. For her, the general characteristic of all systems is very important: the presence of information transfer and management processes in them. Kazakhstan's legislation is undergoing numerous reforms. The legal analysis of the legal system is ambiguous. There is quite a considerable palette of opinions regarding the understanding of this important category. Reproducing them may resemble a routine inventory of different points of view. But each of them represents a special approach to a complex problem, a special cross-section of legal reality, revealing different and collectively diverse sides, signs, properties, functions. The legal system of the Republic of Kazakhstan is constantly in dynamic development. The general characteristic of all existing systems is very important: the presence of information transfer and management processes in them. Scientific research of actual problems of the legal system, its conceptual and categorical apparatus, structural organization, internal and external relationships, its place in society, as well as its role as the most important factor in the existence and development of societies is always extremely relevant.Key words: the legal system, the system of law, the rule of law, the system of legislation, public law, legal policy, private law, legal mechanisms, legal means, the rule of law.